Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1074/jbc.273.45.29811
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ethanol on the Plasma Membrane Calcium Pump Is Isoform-specific

Abstract: The effect of ethanol has been studied on four different isoforms of the plasma membrane Ca 2؉ -ATPase expressed in Sf9 cells with the help of the baculovirus system. The PMCA2CI protein was maximally activated by 0.5% ethanol, a concentration 8 -10 times lower than that needed to obtain the same effect on the PMCA4 protein or on the pump of erythrocyte membranes, which is a mixture of isoforms 1 and 4. Experiments performed with truncated pumps indicated that the stimulation by ethanol was lost if the C-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The locus of interaction of the Ca# + -ATPase with CaM is well documented [3], whereas we have reported that ethanol interacts with a section of the enzyme in the C-terminal domain that is comprised of at least 95 amino acids [15]. Taking into account the presence of two hydroxy groups in the ceramide molecule, we expected that the mechanism of action of this lipid to be the same as that of ethanol.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The locus of interaction of the Ca# + -ATPase with CaM is well documented [3], whereas we have reported that ethanol interacts with a section of the enzyme in the C-terminal domain that is comprised of at least 95 amino acids [15]. Taking into account the presence of two hydroxy groups in the ceramide molecule, we expected that the mechanism of action of this lipid to be the same as that of ethanol.…”
Section: Discussionmentioning
confidence: 92%
“…We have shown previously that ethanol is able to stimulate this pump to a greater extent than all the effectors mentioned above [14,15]. Interestingly, this effect is additive to that of CaM, which indicates that CaM and ethanol stimulate the enzyme by different mechanisms [14,15]. However, ethanol is not a physiological effector.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We have shown that ethanol is able to stimulate this pump to a higher level than all the effectors previously mentioned [13,14]. Ethanol effect on the PMCA, besides being isoform-specific [14] is additive to that of CaM, which indicates that these two effectors stimulate the enzyme by different mechanisms. Because ethanol is not a physiological effector, we sought for an endogenous compound capable to induce similar effects on the calcium pump.…”
mentioning
confidence: 61%
“…Beside, the PMCA can also be stimulated by controlled proteolysis, organic solvents and auto-aggregation of the enzyme [10-12]. We have shown that ethanol is able to stimulate this pump to a higher level than all the effectors previously mentioned [13,14]. Ethanol effect on the PMCA, besides being isoform-specific [14] is additive to that of CaM, which indicates that these two effectors stimulate the enzyme by different mechanisms.…”
mentioning
confidence: 87%